2020
DOI: 10.1186/s11671-020-3267-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface Proton Conduction of Sm-Doped CeO2-δ Thin Film Preferentially Grown on Al2O3 (0001)

Abstract: Sm-doped CeO 2-δ (Ce 0.9 Sm 0.1 O 2-δ ; SDC) thin films were prepared on Al 2 O 3 (0001) substrates by radio frequency magnetron sputtering. The prepared thin films were preferentially grown along the [111] direction, with the spacing of the (111) plane (d 111) expanded by 2.6% to compensate for a lattice mismatch against the substrate. The wet-annealed SDC thin film, with the reduced d 111 value, exhibited surface protonic conduction in the lowtemperature region below 100°C. The O1s photoemission spectrum exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Two filled curves of the PES spectrum are the O 2and OHpeaks expected from Gaussian fitting, and the fitting curve of the solid line, which corresponds to the sum of the two filled ones, in accordance with the PES spectrum. Such an OHpeak is often observed in surface proton conducting oxides 33,34) and carrier-doped TiO 2 thin film. 19) The appearance of the OHpeak reflects that the proton taken from the sputtering ceramic target plays a useful role as ion carriers of electron-ion mixed conduction indicated in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Two filled curves of the PES spectrum are the O 2and OHpeaks expected from Gaussian fitting, and the fitting curve of the solid line, which corresponds to the sum of the two filled ones, in accordance with the PES spectrum. Such an OHpeak is often observed in surface proton conducting oxides 33,34) and carrier-doped TiO 2 thin film. 19) The appearance of the OHpeak reflects that the proton taken from the sputtering ceramic target plays a useful role as ion carriers of electron-ion mixed conduction indicated in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Our group has also reported that the Ce 0.90 Sm 0.10 O 2−δ thin film has large amount of oxygen vacancies, which activates surface proton conduction of σT ∼ 1.0 × 10 0 Scm −1 K at 25 °C, in the (111) plane. 19,20) These results indicate that the hydrophilicity of the oxide surface strongly depends on the presence of an oxygen vacancy.…”
Section: Introductionmentioning
confidence: 83%
“…Taking advantage of this sputtering method, we have achieved to prepare several oxide proton conductor thin films, including YSZ and Sm-doped CeO 2 , and have been able to achieve higher ionic conductivity. 19,20,[22][23][24] If the CeO 2-δ thin film exhibits higher ionic conductivity than bulk ceramic, it may become an electrolyte film for proton ceramic fuel cells or EDLT device.…”
Section: Introductionmentioning
confidence: 99%
“…While there are still challenges to address, such as the minimization of leakage currents and the enhancement of the on/off ratio, the outcomes of this study illustrate the enormous potential of the redox-transistor-based artificial synapse, since the introduction of current pulse control to many previously reported redox-transistor-based artificial synaptic devices could dramatically improve their performance. Redox-transistors offer unique physical properties that can be controlled by combining any electrolyte material with any channel semiconductor material, and also by utilizing the nanostructure of the material [62][63][64][65][66][67][68]. Such diversity in material selection and the physical properties of redox-transistors opens up the possibility of developing redox-based artificial synaptic devices.…”
Section: Discussionmentioning
confidence: 99%